A1S_2811, a CheA/Y‐like hybrid two‐component regulator from Acinetobacter baumannii ATCC17978, is involved in surface motility and biofilm formation in this bacterium. Issue 5 (17th July 2017) - Chen, Rong; Lv, Ruichen; Xiao, Lisheng; Wang, Min; Du, Zongmin; Tan, Yafang; Cui, Yujun; Yan, Yanfeng; Luo, Yanping; Yang, Ruifu; Song, Yajun
Abstract: Two‐component systems in Acinetobacter baumannii are associated with its virulence, drug resistance, motility, biofilm formation, and other characteristics. In this study, we used RecAb, a genetic engineering method, to investigate the function of A1S_2811 in A. baumannii strain ATCC17978. A1S_2811, a hypothetical hybrid sensor histidine kinase/response regulator, has four histidine‐containing phosphotransfer domains, a CheA‐like regulatory domain, and a CheY‐like receiver domain at its C terminus. Compared with the ATCC17978 strain, both surface motility and biofilm formation at the gas–liquid interface decreased significantly in the A1S_2811 knock‐out strain. The number of pilus‐like structures and the amount of extrapolymeric substances on the cell surface also decreased in the A1S_2811 null strain. Transcription of abaI, which encodes an N ‐acylhomoserine lactone synthase in A. baumannii, decreased significantly in the A1S_2811 null strain, and supplementation with synthetic N ‐(3‐oxodecanoyl) homoserine‐l ‐lactone rescued the surface motility and biofilm formation phenotype in the null mutant. We speculate that A1S_2811 regulates surface motility and biofilm formation, not by regulating type IV pili‐associated genes expression, but by regulating the chaperone/usher pili‐associated csuA/ABCDE operon and the AbaI‐dependent quorum‐sensing pathway‐associated A1S_0112‐0119 operon instead. Abstract : A1S_2811 regulates surface motility and biofilm formation not by regulating the expression of genes associated with type IV pili, but regulating the csuA/BABCDE operon associated with CU pili and A1S_0112‐0119 operon associated with AbaI‐dependent quorum‐sensing pathway instead.